2011
DOI: 10.20502/rbg.v12i2.230
|View full text |Cite
|
Sign up to set email alerts
|

A Influência Da Topografia Na Distribuição De Gramíneas Em Um Fragmento De Floresta Atlântica Urbana Montanhosa – Maciço Da Tijuca/Rj

Abstract: ResumoUm importante mas ainda pouco compreendido fator de influência na dinâmica florestal em áreas montanhosas é a topografia. O objetivo deste estudo foi analisar a distribuição espacial de manchas de gramíneas no fragmento de floresta atlântica urbana que recobre o Maciço da Tijuca, levando em conta os aspectos topográficos. Foi feito um mapeamento de uso e cobertura com base em ortofotos aéreas de 2004, e, com o auxílio de um Modelo Digital de Elevação, foram realizadas algumas análises espaciais (mensuraç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Field observations guided the choice of monitored depths, as well as previously developed studies that sought to compare different coverages, mainly between forested and pasture areas, such as Jansen (2001), Silveira (2004), Dias and Coelho Netto (2011) and Marques et al (2018). In addition, it was observed that the grassroots (Brachiaria) root matrix were concentrated up to a depth of 40 cm, corroborating the survey carried out by Cambra and Coelho Netto (2000) in the neighboring basin (Bananal River).…”
Section: Monitoring Of Suction In the Unsaturated Zone In Drainage He...mentioning
confidence: 99%
“…Field observations guided the choice of monitored depths, as well as previously developed studies that sought to compare different coverages, mainly between forested and pasture areas, such as Jansen (2001), Silveira (2004), Dias and Coelho Netto (2011) and Marques et al (2018). In addition, it was observed that the grassroots (Brachiaria) root matrix were concentrated up to a depth of 40 cm, corroborating the survey carried out by Cambra and Coelho Netto (2000) in the neighboring basin (Bananal River).…”
Section: Monitoring Of Suction In the Unsaturated Zone In Drainage He...mentioning
confidence: 99%